تأثير تمارين هوائية بإيقاع الزومبا في تحسين المطاولة العامة وبعض المتغيرات الكيمو حيوية وVO2max والاستشفاء لدى ممارسي النشاط الرياضي - غفوری, ریباز بایز توفیق; قادر, یاسین عبدالمناف; حسن, مازن سامی (Sulaimani Journal for Humanities, 2023)
Zumba exercises are one of the modern trends in training methods, as its movements are characterized by spontaneity, beauty, and harmony in harmony with the music, which encourages individuals to practice it as a physical activity or for excellence. The study aimed to reveal the effect of a curriculum of aerobic exercises accompanied by music with the rhythm of Zumba on improving some biochemical variables, the maximum value of oxygen consumption, general stamina, and recovery for sports activity practitioners. The researchers used the experimental approach with the pre-and post-measurement design, as the research community consisted of second-stage students in the physical education faculty at Koya University, while the research sample consisted of 18 students in the physical education faculty, three of whom were excluded for not adhering to the training program. Low-intensity interval training was used based on the schedule prepared by Fox and Matthews for a period of two months at the rate of three training units per week with a load wave of (3:1) g. The results of the study were also analysed using the SPSS statistical bag to find out the level of statistical significance. The most important conclusions reached by the study were the presence of statistically significant differences between the pre- and post-measurements in favour of post-measurement via improvement of general stamina, the increase in the number of red blood cells, the percentage of haemoglobin and the speed of return of the heart rate during the recovery period for a sample of an individual's search for three minutes (1,3, and 5).